Evaluation of a novel content-based image retrieval system for the differentiation of interstitial lung diseases in CT examinations - Pogarell, Tobias; Bayerl, Nadine; Wetzl, Matthias; Roth, Jessica; Speier, Christoph; Uder, Michael; Dankerl, Peter; Cavallaro, Alexander Josef (Diagnostics, 2021)
To evaluate the reader’s diagnostic performance against the ground truth with and without the help of a novel content-based image retrieval system (CBIR) that retrieves images with similar CT patterns from a database of 79 different interstitial lung diseases. We evaluated three novice readers’ and three resident physicians‘ (with at least three years of experience) diagnostic performance evaluating 50 different CTs featuring 10 different patterns (e.g., honeycombing, tree-in bud, ground glass, bronchiectasis, etc.) and 24 different diseases (sarcoidosis, UIP, NSIP, Aspergillosis, COVID-19 pneumonia etc.). The participants read the cases first without assistance (and without feedback regarding correctness), and with a 2-month interval in a random order with the assistance of the novel CBIR. To invoke the CBIR, a ROI is placed into the pathologic pattern by the reader and the system retrieves diseases with similar patterns. To further narrow the differential diagnosis, the readers can consult an integrated textbook and have the possibility of selecting high-level semantic features representing clinical information (chronic, infectious, smoking status, etc.). We analyzed readers’ accuracy without and with CBIR assistance and further tested the hypothesis that the CBIR would help to improve diagnostic performance utilizing Wilcoxon signed rank test. The novice readers demonstrated an unassisted accuracy of 18/28/44%, and an assisted accuracy of 84/82/90%, respectively. The resident physicians demonstrated an unassisted accuracy of 56/56/70%, and an assisted accuracy of 94/90/96%, respectively. For each reader, as well as overall, Sign test demonstrated statistically significant (p < 0.01) difference between the unassisted and the assisted reads. For students and physicians, Chi2-test and Mann-Whitney-U test demonstrated statistically significant (p < 0.01) difference for unassisted reads and statistically insignificant (p > 0.01) difference for assisted reads. The evaluated CBIR relying on pattern analysis and featuring the option to filter the results of the CBIR by predominant characteristics of the diseases via selecting high-level semantic features helped to drastically improve novices’ and resident physicians’ accuracy in diagnosing interstitial lung diseases in CT.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Computed tomography; Computer-aided diagnosis; Content-based image retrieval; Interstitial lung disease

Evaluation of ct-guided ultra-low-dose protocol for injection guidance in preparation of mr-arthrography of the shoulder and hip joints in comparison to conventional and low-dose protocols - Goeller, Anja; Pogarell, Tobias; May, Matthias; Uder, Michael; Dankerl, Peter (Diagnostics, 2021)
To evaluate patients’ radiation exposure undergoing CT-guided joint injection in preparation of MR-arthrography. We developed a novel ultra-low-dose protocol utilizing tin-filtration, performed it in 60 patients and compared the radiation exposure (DLP) and success rate to conventional protocol (26 cases) and low-dose protocol (37 cases). We evaluated 123 patients’ radiation exposure undergoing CT-guided joint injection from 16 January–21 March. A total of 55 patients received CT-guided joint injections with various other examination protocols and were excluded from further investigation. In total, 56 patients received shoulder injection and 67 received hip injection with consecutive MR arthrography. The ultra-low-dose protocol was performed in 60 pa-tients, the low-dose protocol in 37 patients and the conventional protocol in 26 patients. We compared the dose of the interventional scans for each protocol (DLP) and then evaluated success rate with MR-arthrography images as gold standard of intraarticular or extracapsular contrast injection. There were significant differences when comparing the DLP of the ultra-low-dose protocol (DLP 1.1 ± 0.39; p < 0.01) to the low dose protocol (DLP 5.3 ± 3.24; p < 0.01) as well as against the conventional protocol (DLP 22.9 ± 8.66; p < 0.01). The ultra-low-dose protocol exposed the patients to an average effective dose of 0.016 millisievert and resulted in a successful joint injection in all 60 pa-tients. The low dose protocol as well as the conventional protocol were also successful in all patients. The presented ultra-low-dose CT-guided joint injection protocol for the preparation of MR-arthrog-raphy demonstrated to reduce patients’ radiation dose in a way that it was less than the equivalent of the natural radiation exposure in Germany over 3 days—and thereby, negligible to the patient.
CRIS-Team Scopus Importer:2021-10-22
Keywords: CT intervention; Joint injection; MR-arthrography; Radiation exposure; Radiation protection; Tin-filtration

Imaging of muscle injuries in soccer - Heiß, Rafael; Tol, Johannes L.; Pogarell, Tobias; Roemer, Frank; Reurink, Guus; Renoux, Jerome; Crema, Michel D.; Guermazi, Ali (Skeletal Radiology, 2023)
Accurate diagnosis of muscle injuries is a challenge in everyday clinical practice and may have profound impact on the recovery and return-to-play decisions of professional athletes particularly in soccer. Imaging techniques such as ultrasound and magnetic resonance imaging (MRI), in addition to the medical history and clinical examination, make a significant contribution to the timely structural assessment of muscle injuries. The severity of a muscle injury determined by imaging findings has a decisive influence on therapy planning and affects prognosis. Imaging is of high importance when the diagnosis or grade of injury is unclear, when recovery is taking longer than expected, and when interventional or surgical management may be needed. This narrative review will discuss ultrasound and MRI for the assessment of sports-related muscle injuries in the context of soccer, including advanced imaging techniques, with the focus on the clinical relevance of imaging findings for the prediction of return to play.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Magnetic resonance imaging; Muscle; Muscle injury; Return to play; Soccer; Sports injuries; Ultrasound

Imaging of the musculoskeletal system using low-field magnetic resonance imaging - Pogarell, Tobias; May, Matthias; Nagel, Armin Michael; Uder, Michael; Heiß, Rafael (Radiologe, 2022)
Background Magnetic resonance imaging (MRI) plays a crucial role in musculoskeletal imaging. The high prevalence and pain-related suffering of patients pose a particular challenge concerning availability and turnover times, respectively. Low-field (<= 1.0 T) MRI has the potential to fulfill these needs. However, during the past three decades, high field systems have increasingly replaced low field systems because of their limitations in image quality. Recent technological advancements in high-performance hard- and software promise musculoskeletal imaging with adequate quality at lower field strengths for several regions and indications. Objectives The goal is to provide insight into the advantages and disadvantages of low-field musculoskeletal imaging, discuss the current literature, and include our first experiences with a modern 0.55 T MRI. Materials and methods This review is based on research in various literature databases and our own musculoskeletal imaging experiences with a modern 0.55 T scanner. Conclusion Most publications pertaining to musculoskeletal imaging at low-field strength MRI are outdated, and studies regarding the diagnostic performance of modern low-field MRI systems are needed. These new systems may complement existing high-field systems and make MRI more accessible, even in low-income countries. From our own experience, modern low-field MRI seems to be adequate in musculoskeletal imaging, especially in acute injuries.
CRIS-Team WoS Importer:2022-04-29
Keywords: Field strength; Musculoskeletal injuries; Image quality; Cost; Sustainability

Impact of intravenous CT contrast agents on internal calibration techniques to determine trabecular BMD of the lumbar spine - Bartenschlager, Stefan; Cavallaro, Alexander Josef; Pogarell, Tobias; Uder, Michael; Chaudry, Oliver; Schett, Georg; Engelke, Klaus (European Journal of Radiology, 2025)
Objectives: Contrast agents are frequently administered in computed tomography (CT) scans used for opportunistic screening of osteoporosis. The objective of this study is to compare the impact of contrast-related bone mineral density (BMD) increase between phantom-based and internal CT calibration techniques. Materials and Methods: Phantom-based and internal CT calibration techniques were used to determine trabecular BMD in 93 existing clinical CT scans of the lumbar spine of 34 subjects, scanned before and after administration of contrast agents. BMD differences between native (Nat) and contrast-enhanced scans in arterial (Art) and portal venous (PV) phases were compared among calibration methods. Three pairs of internal reference materials were investigated: blood/air, subcutaneous adipose tissue (SAT)/air and muscle tissue/air. Results: Contrast agents increased CT values of blood in the aorta and the inferior vena cava in the Art phase by 210 ± 99HU and 47 ± 35HU, respectively and in the PV phase by 110 ± 49HU and 73 ± 28HU, respectively. Effects on CT values of muscle and SAT were < 5HU in the Art phase and < 10HU in the PV phase. BMD obtained with phantom calibration increased significantly (p < 0.01) in Art and PV phases by 8.6 ± 14.7 mg/cm3 and 14.4 ± 16.3 mg/cm3, respectively. If SAT/air or muscle/air were used as internal reference materials, increases in internally calibrated BMD (<12 mg/cm3 in AT phase and < 17 mg/cm3 in PV phase) did not significantly differ (p > 0.1 for Art and PV phases) from increases of phantom-calibrated BMD. Conclusions: Although CT values of internal reference materials increased following the administration of contrast, internal calibration was unable to mitigate the contrast-related BMD increases observed in phantom-based calibration.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Computed tomography; Contrast agents; Internal BMD calibration; Lumbar spine; Osteoporosis; Opportunistic screening

Modern low-field MRI - Pogarell, Tobias; Heiß, Rafael; Janka, Rolf Matthias; Nagel, Armin Michael; Uder, Michael; Roemer, Frank (Skeletal Radiology, 2024)
This narrative review explores recent advancements and applications of modern low-field (≤ 1 Tesla) magnetic resonance imaging (MRI) in musculoskeletal radiology. Historically, high-field MRI systems (1.5 T and 3 T) have been the standard in clinical practice due to superior image resolution and signal-to-noise ratio. However, recent technological advancements in low-field MRI offer promising avenues for musculoskeletal imaging. General principles of low-field MRI systems are being introduced, highlighting their strengths and limitations compared to high-field counterparts. Emphasis is placed on advancements in hardware design, including novel magnet configurations, gradient systems, and radiofrequency coils, which have improved image quality and reduced susceptibility artifacts particularly in musculoskeletal imaging. Different clinical applications of modern low-field MRI in musculoskeletal radiology are being discussed. The diagnostic performance of low-field MRI in diagnosing various musculoskeletal pathologies, such as ligament and tendon injuries, osteoarthritis, and cartilage lesions, is being presented. Moreover, the discussion encompasses the cost-effectiveness and accessibility of low-field MRI systems, making them viable options for imaging centers with limited resources or specific patient populations. From a scientific standpoint, the amount of available data regarding musculoskeletal imaging at low-field strengths is limited and often several decades old. This review will give an insight to the existing literature and summarize our own experiences with a modern low-field MRI system over the last 3 years. In conclusion, the narrative review highlights the potential clinical utility, challenges, and future directions of modern low-field MRI, offering valuable insights for radiologists and healthcare professionals seeking to leverage these advancements in their practice.
CRIS-Team Scopus Importer:2024-03-01
Keywords: 0.55 Tesla; Field strength; Joints; Knee; Low-field; MRI; Musculoskeletal radiology

Opportunistic Screening With CT: Comparison of Phantomless BMD Calibration Methods - Bartenschlager, Stefan; Cavallaro, Alexander Josef; Pogarell, Tobias; Chaudry, Oliver; Uder, Michael; Khosla, Sundeep; Schett, Georg; Engelke, Klaus (Journal of Bone and Mineral Research, 2023)
Opportunistic screening is a new promising technique to identify individuals at high risk for osteoporotic fracture using computed tomography (CT) scans originally acquired for an clinical purpose unrelated to osteoporosis. In these CT scans, a calibration phantom traditionally required to convert measured CT values to bone mineral density (BMD) is missing. As an alternative, phantomless calibration has been developed. This study aimed to review the principles of four existing phantomless calibration methods and to compare their performance against the gold standard of simultaneous calibration (ΔBMD). All methods were applied to a dataset of 350 females scanned with a highly standardized CT protocol (DS1) and to a second dataset of 114 patients (38 female) from clinical routine covering a large range of CT acquisition and reconstruction parameters (DS2). Three of the phantomless calibration methods must be precalibrated with a reference dataset containing a calibration phantom. Sixty scans from DS1 and 57 from DS2 were randomly selected for this precalibration. For each phantomless calibration method first the best combination of internal reference materials (IMs) was selected. These were either air and blood or subcutaneous adipose tissue, blood, and cortical bone. In addition, for phantomless calibration a fifth method based on average calibration parameters derived from the reference dataset was applied. For DS1, ΔBMD results (mean (Formula presented.) standard deviation) for the phantomless calibration methods requiring a precalibration ranged from 0.1 (Formula presented.) 2.7 mg/cm3 to 2.4 (Formula presented.) 3.5 mg/cm3 with similar means but significantly higher standard deviations for DS2. Performance of the phantomless calibration method, which does not require a precalibration was worse (ΔBMD DS1: 12.6 (Formula presented.) 13.2 mg/cm3, DS2: 0.5 (Formula presented.) 8.8 mg/cm3). In conclusion, phantomless BMD calibration performs well if precalibrated with a reference dataset. © 2023 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).
CRIS-Team Scopus Importer:2023-10-20
Keywords: BONE MINERAL DENSITY; PERFORMANCE OF PHANTOMLESS CALIBRATION; OPPORTUNISTIC SCREENING; SIMULTANEOUS CALIBRATION

Response to the editor of JBMR regarding the letter related to "Opportunistic screening with CT: comparison of phantomless BMD calibration methods". - Bartenschlager, Stefan; Cavallaro, Alexander Josef; Pogarell, Tobias; Chaudry, Oliver; Uder, Michael; Khosla, Sundeep; Schett, Georg; Engelke, Klaus (Journal of Bone and Mineral Research, 2024)
EVALuna2:570800